Effects of psychosis-associated genetic markers on brain volumetry: a systematic review of replicated findings and an independent validation. Issue 16 (28th December 2022) - Vouga Ribeiro, Nuno; Tavares, Vânia; Bramon, Elvira; Toulopoulou, Timothea; Valli, Isabel; Shergill, Sukhi; Murray, Robin; Prata, Diana
Abstract: Background: Given psychotic illnesses' high heritability and associations with brain structure, numerous neuroimaging-genetics findings have been reported in the last two decades. However, few findings have been replicated. In the present independent sample we aimed to replicate any psychosis-implicated SNPs (single nucleotide polymorphisms), which had previously shown at least two main effects on brain volume. Methods: A systematic review for SNPs showing a replicated effect on brain volume yielded 25 studies implicating seven SNPs in five genes. Their effect was then tested in 113 subjects with either schizophrenia, bipolar disorder, 'at risk mental state' or healthy state, for whole-brain and region-of-interest (ROI) associations with grey and white matter volume changes, using voxel-based morphometry. Results: We found FWER-corrected (Family-wise error rate) (i.e. statistically significant) associations of: (1) CACNA1C -rs769087-A with larger bilateral hippocampus and thalamus white matter, across the whole brain; and (2) CACNA1C -rs769087-A with larger superior frontal gyrus, as ROI. Higher replication concordance with existing literature was found, in decreasing order, for: (1) CACNA1C -rs769087-A, with larger dorsolateral-prefrontal/superior frontal gyrus and hippocampi (both with anatomical and directional concordance); (2) ZNF804A -rs11681373-A, with smaller angular gyrus grey matter and rectus gyri white matter (both with anatomical and directional concordance); and (3) BDNF- rs6265-T with superior frontal and middle cingulate gyri volume change (with anatomical and allelic concordance). Conclusions: Most literature findings were not herein replicated. Nevertheless, high degree/likelihood of replication was found for two genome-wide association studies- and one candidate-implicated SNPs, supporting their involvement in psychosis and brain structure.